Business Development Strategy Analysis Using the Business Model Canvas Approach at Genong Farm Madiun - Susanto, Irvan; Hartono, Sri; Abrianto, Tegoeh Hari (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to analyze and recommend business development strategies for Genong Farm Madiun using the Business Model Canvas approach. The method used is descriptive qualitative, with data collection through observation, interviews, documentation, and triangulation. Data is analyzed using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and verification. The research results identify that the business model of Genong Farm Madiun encompasses nine elements of the Business Model Canvas: Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. Based on this analysis, strategic recommendations are provided for each element to enhance business operational effectiveness and efficiency. This research provides valuable insights into how Genong Farm Madiun can optimize its business model to achieve sustainable growth and increase market competitiveness. The recommendations given are expected to assist Genong Farm Madiun in designing better and more innovative business strategies.